Eat your rocks, Croc! : Dr. Glider's advice for troubled animals - Keating, Jess (Orchard Books, an imprint of Scholastic Inc., 2020)
Dr. Sugar Glider, a small Australian possum, travels around the world (even underwater) dispensing good advice to animals with problems, including a crocodile with a stomach ache, a stressed out meerkat mom, and a male praying mantis looking for a date--while avoiding being eaten.